Kolaborasi Negara dan Sektor Privat dalam Peningkatan Kapasitas Pemuda Melalui Pelatihan Perencanaan Acara - Kharis, Ahmad; Wibowo, Kristri Priyantara; Yusuf, Muhamad Fahrudin (Kifah: Jurnal Pengabdian Masyarakat, 2025)
This program is designed with a participatory approach to ensure active involvement of participants in every stage of the training. The purpose of this service is to enhance the skills of young people through Event Planner training as a practical skills development step aimed at building the local creative economy. The method used is Participatory Learning and Action (PLA), with data collection techniques through observation, in-depth interviews, and questionnaires. This service also evaluates the effectiveness of collaboration in building individual competencies in event planning, opening new business opportunities, and strengthening the creative industry ecosystem. The collaboration between the Salatiga City Youth and Sports Office and Sasana Suluh Kabudayan Consultant has proven effective in creating synergy among stakeholders, providing applicable training materials, and delivering significant social and economic impacts for the community. Similar programs are recommended to be replicated in other areas to improve the competitiveness of communities in the creative economy sector and support sustainable development. The research results show that Event Planner training not only enhances participants' technical understanding of event management but also encourages their active participation in the community. These findings emphasize the importance of cross-sector partnerships in community capacity building. This service aims to increase youth capacity through Event Planner training as an effort to develop practical skills oriented towards empowering the local creative economy. Therefore, similar programs are recommended to be replicated in other areas to enhance community competitiveness in the Creative Economy sector and support Sustainable Development.